Identificación de áreas prioritarias para la conservación de reptiles en Michoacán y evaluación del impacto del cambio climático - Nava González, Bisbrian Alhelí (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The destruction and degradation of natural habitats is causing the extinction of many species. To the impact of habitat loss and degradation, the potential impact that climate change may have on biodiversity is added. Information is urgently needed to enable the design of efficient conservation areas to protect the most important areas for biodiversity conservation, according to the current scenario and future derivatives of climate change predictions. This information is particularly critical in the case of organisms whose ecological and physiological conditions make them more susceptible to be affected by sources of disturbance relating human origin. In this study, species distribution modeling techniques are applied to identify areas of suitable habitat overlap, from the climatic point of view, to the reptile species. Moreover, the impact that climate change may have on the distribution of these areas of suitable habitat is evaluated. A database was purified (review of its geo referencing, taxonomic nomenclature and collection period) until 1479 presence records were collected. Of the 19 bioclimatic variables available, 7 were selected and used, together with the records of presence, to generate distribution models for 58 species. In each model, the most appropriate habitat area was identified. Moreover, predictive distribution models were generated for 2050, using the projected scenarios A2 and B1. Each model was reclassified to define the area more suitable habitat. Areas of more suitable habitat for the species were overlapped to define areas of agreement, and the degree of coverage offered by the NPAs in the state.

La destrucción y degradación de los hábitats naturales esta? causando la extinción de una gran cantidad de especies. Al impacto, causado por la pérdida y degradación del hábitat, se agrega el impacto potencial que el cambio climático puede tener sobre la biodiversidad. Resulta urgente, contar con información que permita diseñar áreas de conservación eficientes, que protejan las zonas más importantes para conservar la biodiversidad de acuerdo al escenario actual y a los futuros, derivados de las predicciones de cambio climático. Esta información es particularmente crítica en el caso de organismos que por sus condiciones ecológicas y fisiológicas resultan más susceptibles a ser afectados por los impactos de las fuentes de perturbación de origen humano referidas. En este estudio, se aplican técnicas de modelado de distribución de especies para por una parte, identificar las zonas donde coincide él hábitat adecuado, desde el punto de vista climático, para las especies de reptiles y por otra parte, evaluar el impacto que el cambio climático puede tener sobre la distribución de estas áreas de hábitat adecuado. Se recopilo? una base de datos que se depuro? (revisión de su georreferencia, nomenclatura taxonómica y periodo de colecta) hasta conseguir 1479 registros de presencia. Se seleccionaron 7 variables bioclimáticas de 19 disponibles, las cuales se utilizaron con los registros de presencia para generar modelos de distribución actual para 58 especies.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2014-0429; Hábitat; Clima; Especies; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1704